Tin(IV) oxide nanoparticles as a saturable absorber for a Q-switched erbium-doped fiber laser - Siddiq, Nur Abdillah; Chong, Wu Yi; Yap, Yuen Kiat; Pramono, Yono Hadi; Ahmad, Harith (IOP Publishing, 2018)
We demonstrate a passively Q-switched erbium-doped fiber laser using a tin(IV) oxide (SnO 2 ) nanoparticle layer as a saturable absorber. A SnO 2 nanoparticle is composited with polyvinyl alcohol (PVA) to form thin saturable absorber film and is sandwiched between fiber ferrules in a ring fiber laser cavity to produce stable, self-started Q-switched laser operation. Q-switched pulsing occurs for pump power between 38 mW and 106 mW. Repetition rate of the laser increases with pump power from 35.4 kHz to 65.6 kHz and the pulse width narrows from 7.64 μs to 2.92 μs. The maximum pulse energy and average output power achieved are 72.11 nJ and 4.73 mW, respectively. Utilizing a tunable bandpass filter, tunable Q-switched laser operation across the C-band (1521 nm-1565 nm) is demonstrated. The laser output is stable across the entire tuning range.